Liposomes Prepared in Absence of Organic Solvents: Sonication Versus Lipid Film Hydration Method - de Jesus Valle, M. J.; Sanchez Navarro, A. (Current Pharmaceutical Analysis, 2015)
Context: Liposomes appear as an excellent vehicle for parenteral and non-parenteral administration routes. Drugs, genetic vaccines or skin care products, are candidates to be included in liposomes. Irrespective of the therapeutic aim, most reported procedures for lipid vesicles formulation, make it necessary to use and then remove organic solvents. Objetive: To explore the possibility of avoiding organic solvents for liposomes preparation by sonication of component mixture. Materials and methods: Liposomes were prepared by direct sonication of lipids and water medium and by the lipid film hydration method both in the presence and absence of trehalose. Extrusion through 1.0 and 0.1 μm pore membranes was performed in both cases. Liposomes size distribution was determined by dynamic laser scattering analysis. Results: Sonication of watery lipid dispersion produces lipid vesicles in a size range of 20-120 nm while lipid film hydration method provides with larger vesicles under all experimental assayed conditions. Extrusion through 1.0 μm pore membrane failed to produce monodisperse liposomes even from the largest liposomes. Sequential extrusion though 0.1 μm, however, lead to monodisperse samples with both methods. Conclusion: The sonication of aqueous lipid dispersions is a suitable organic solvent-free alternative for preparation of small lipid vesicles.
Keywords: liposomes